PROGRAM LABORATORIUM PENGOLAHAN SAMPAH SEBAGAI PENGUATAN NILAI PENDIDIKAN KARAKTER ISLAM DI PESANTREN KEBON JAMBU - Tafsir Tantowi; Diniyatus Salamah, Fitriah, Muhammad Aulia Taufiqi (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
Character education is at the heart of the Islamic education system, emphasizing not only academic intelligence but also the development of the moral and ethical character of students (santri). Islamic education aims to cultivate a generation that embodies knowledge and noble character. Pesantren (Islamic boarding schools) play a strategic role in enlightening and empowering communities by providing education in religious knowledge alongside essential life skills. These institutions can inspire environmental education, teaching students to love and care for their surroundings. This research assesses the impact of a waste laboratory program in reinforcing the values of Islamic education at Pondok Pesantren Kebon Jambu, focusing on various aspects such as behavioral changes among students, increased awareness of waste management, and contributions to the surrounding environment. A qualitative approach is employed to explore individual experiences and perspectives within the social and cultural context of the pesantren. Through a case study methodology, at Pondok Pesantren Kebon Jambu, this program has successfully educated students about the importance of recycling and waste reduction, while also creating economic benefits through composting organic waste. With commitment and enthusiasm, we can achieve education that prioritizes not only knowledge but also strong character and concern for the environment.